2022
DOI: 10.1186/s10194-022-01488-8
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of low-frequency fluctuation after a single-trigger pain in patients with classical trigeminal neuralgia

Abstract: Objective This study aimed to explore the central mechanism of classical trigeminal neuralgia (CTN) by analyzing the static amplitude of low-frequency fluctuation (sALFF) and dynamic amplitude of low-frequency fluctuation (dALFF) in patients with CTN before and after a single-trigger pain. Methods This study included 48 patients (37 women and 11 men, age 55.65 ± 11.41 years) with CTN. All participants underwent 3D-T1WI and three times resting-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…An ALFF study in patients with classical trigeminal neuralgia (CTN) included 48 patients with CTN found after a single trigger pain, and the ALFF values increased in the bilateral MOG in triggering-5 s and triggering-30 min [ 47 ]. A brain structure study via experimental induction of low back pain found that asymptomatic participants had greater grey matter density at MOG_L than participants with pain [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…An ALFF study in patients with classical trigeminal neuralgia (CTN) included 48 patients with CTN found after a single trigger pain, and the ALFF values increased in the bilateral MOG in triggering-5 s and triggering-30 min [ 47 ]. A brain structure study via experimental induction of low back pain found that asymptomatic participants had greater grey matter density at MOG_L than participants with pain [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 85 CTN patients were recruited from our Hospital. The inclusion criteria for patients with CTN were as follows: (1) the CTN patients were diagnosed according to the ICHD-3 10 ; (2) unilateral pain; (3) paroxysmal facial pain precipitated by trigger factors; (4) conventional magnetic resonance imaging examination revealing no evidence of abnormal brain signals; (5) no additional neurological or sensory deficits in all patients; (6) no previous surgical or other invasive procedures for CTN; (7) no contraindications to MRI scanning; (8) patients underwent microvascular decompression and confirmed that the NVC was existed; and (9) right-handness [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria for patients with CTN were as follows: (1) patients diagnosed with CTN according to the third edition of the International Classification of Headache Disorders (ICHD-3) and demonstration of NVC (not simply contact) on MRI with morphological changes (atrophy or dislocation) in the trigeminal nerve root; (2) unilateral pain in the distribution of one or more branches of the trigeminal nerve; (3) paroxysmal facial pain precipitated by trigger factors (such as light touching of the face and opening mouth); (4) conventional MRI T1 weighted imaging (T1WI) and T2WI examination showed no abnormal brain signals; (5) no additional neurological or sensory deficits in all patients; (6) no previous surgical or other invasive procedures for CTN; (7) no contraindications to MR scanning; (8) patients underwent microvascular decompression and presented NVC which not only contact; (9) right-handed patients. The exclusion criteria were as follows: (1) patients with CTN who had undergone surgical treatment before; (2) headaches and other paroxysmal or chronic pain conditions; (3) a family history of headache or other pain in first-degree relatives; (4) other somatic or psychiatric conditions; (5) left-handedness; (6) contraindications to MRI ( Ge et al, 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…The regional homogeneity (ReHo), the amplitude of low-frequency fluctuation (ALFF), and voxel-based degree centrality (DC) are the data-driven analysis methods of rs-fMRI. ReHo reflects the temporal consistency of spontaneous neural activity between a given voxel and its neighbors ( Zang et al, 2004 ; Ge et al, 2022a ). Wang et al (2015) ; Xiang et al (2019) found that compared to healthy controls (HCs), the ReHo values of multiple brain regions are increased in CTN patients.…”
Section: Introductionmentioning
confidence: 99%